Radical scavenging activity of Chlorophytum borivilianum L. root extract and its protective role in cauda epididymal sperm integrity in Mus musculus after gamma irradiation - Vyas, Ruchi; Kesari, Kavindra Kumar; Lukac, Norbert; Slama, Petr; Roychoudhury, Shubhadeep; Sisodia, Rashmi (Frontiers in Cell and Developmental Biology, 2023)
Chlorophytum borivilianum L. is a recognised medicine for treatment of impotency in South Asian countries. In Ayurveda this plant is used for treatment of multiple health conditions and diseases such as diabetes, infection, and cardiovascular diseases. Parts of plant has been used as excellent antioxidants. Since oxidative stress plays important role in spermatogenesis and fertility in male, this study evaluated role of ethanolic extract of C. borivilianum root (CRE) in epididymal sperm maturation against adversities posed by ionizing radiation. Antioxidative potential of CRE was evaluated through DPPH and NO scavenging assays. Four groups were constituted, labelled as Group I: sham control, Group II: 7 days pre-treatment with 50 mg/kg CRE, Group III: 6 Gy irradiation without pre-treatment, and Group IV: 7 days pre-treatment with 50 mg/kg CRE and 6 Gy irradiation on the 7th day. Animals were observed for 30 days and later sacrificed to evaluate sperm characteristics and morphology. CRE showed remarkable antioxidative potential with IC50 46.37 µg/ml and 98.39 µg/ml for DPPH and NO, respectively. Significant decline (p<0.001) in cauda epididymal sperm count, motility and viability was observed in Group III animals. Group IV also showed substantial decline (p<0.01) in all three parameters comparing to Group I, nonetheless, these were significantly higher when compared with Group III. Morphological alterations indicated coiled and bent tail, with presence of cytoplasmic droplets in Group III, which declined substantial in Group IV. Ultrastructure of sperms indicated higher curvature of hook (>20°) in Group III comparing to Group IV indicating specific interferences in sperm maturation process. It was concluded that pre-treatment with 50 mg/kg body weight of CRE could protect sperms during epididymal maturation against oxidative stress.